Libraries in the Federal Republic of Germany - Busse, Gisela von.; Ernestus, Horst; Plassmann, Engelbert (Wiesbaden : Harrassowitz, 1983)
The book gives account of the libraries in the Federal Republic of Germany. It supplies information about the various types of libraries, their functions, their situation and their administrative procedures among others.
This translation is based on the new (1983) German ed.
Includes index.
Includes bibliographical references: p. 237-255.
usc 14/01/2019
Loans
Keywords: Libraries; Germany (West)